2021
DOI: 10.1080/15374416.2020.1846542
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Specific Techniques in Behavioral Teacher Training for Childhood ADHD: A Randomized Controlled Microtrial

Abstract: Objective: Behavioral teacher training is the most effective classroom-based intervention for children with attention-deficit/hyperactivity disorder (ADHD). However, it is currently unknown which components of this intervention add to its effectiveness and for whom these are effective. Method: In this microtrial, teachers of 90 children with impairing levels of ADHD symptoms (6-12 years) were randomly assigned to one of three conditions: a short (2 sessions), individualized intervention consisting of either (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 71 publications
3
33
1
Order By: Relevance
“…Future studies are needed to test the hypothesis based on our current results that focusing on teaching parents to manipulate antecedents of behavior and to provide positive consequences for desired behavior is particularly effective to change child behavior in ADHD samples. Two recent micro-trials (one for parents and one for teachers) provided evidence in this direction: when provided in isolation, both stimulus control and contingency management techniques were found effective on improving the child's behavior 67,68 . Future studies should further test whether J o u r n a l P r e -p r o o f the current findings also apply for child outcomes, as the ultimate goal of parent training is to change the child's behavior via parental behavior.…”
Section: J O U R N a L P R E -P R O O F 22mentioning
confidence: 98%
“…Future studies are needed to test the hypothesis based on our current results that focusing on teaching parents to manipulate antecedents of behavior and to provide positive consequences for desired behavior is particularly effective to change child behavior in ADHD samples. Two recent micro-trials (one for parents and one for teachers) provided evidence in this direction: when provided in isolation, both stimulus control and contingency management techniques were found effective on improving the child's behavior 67,68 . Future studies should further test whether J o u r n a l P r e -p r o o f the current findings also apply for child outcomes, as the ultimate goal of parent training is to change the child's behavior via parental behavior.…”
Section: J O U R N a L P R E -P R O O F 22mentioning
confidence: 98%
“…Because there are no guidelines for reporting on microtrials, we used the CONSORT guidelines for reporting on randomized controlled trials (Moher et al, 2001). More details on the design of the study are available in Staff et al (2021). This study was registered at the Dutch Trial Register: https:// www.…”
Section: Designmentioning
confidence: 99%
“…In a previous article of our group (Staff et al, 2021), we analyzed our randomized controlled microtrial using an ecologically momentary assessment (EMA) measure of behavior as outcome measure (Shiffman et al, 2008). Four preselected individual problem behaviors in a specific situation were assessed, and two of these were directly targeted in the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that for younger children, emergency management techniques were more effective than stimulus control techniques, whilst for older children, quite the opposite was true. Furthermore, the effectiveness of the emergency management-based technique increased as the number of students per class decreased, whilst the effectiveness of stimulus control-based techniques did not depend on the size of the class (Staff et al, 2021).…”
Section: Behavioral Interventionsmentioning
confidence: 94%
“…In the emergency management intervention, the teachers were taught techniques to display specific behaviors, such as praise, reward, ignorance, and negative consequences. The plan of intervention in this case may consist of: (1) the teacher rewarding frequently the child's expected behavior (e.g., praise when the child is working or quiet), (2) the teacher praising other children who are concentrated in their work and (3) the teacher ignoring persisting attentionseeking behaviors (e.g., hand raising, calling the teacher's name) (Staff et al 2021).…”
Section: Behavioral Interventionsmentioning
confidence: 99%